Arsitektur hijau mendukung adaptasi perilaku di masa pandemi Coronavirus disease (COVID-19) di Alun-Alun Kota Batam - Leony, Melinda; Sari, Suzanna Ratih (Dinamika Lingkungan Indonesia, 2022)
This study aims to determine the principles of a green architecture approach that can support behavior change during the Covid-19 pandemic and to determine the arrangement of green architecture that can support behavior change during the Covid-19 pandemic in Batam City Square. This research method is to use literature study. The results show that in the Covid-19 pandemic maintaining environmental health is very crucial for our physical & mental health, and the concept of green buildings is a way to create environmentally or ecologically friendly buildings. To achieve a balance between systems, interactions between humans and the environment. Spatial planning and design using the green building method in Batam City Square is expected to be able to overcome and minimize adverse impacts on human health and the environment, as well as overcome Covid-19 promotion efforts. With a development concept based on keeping your distance and washing your hands, an artistic and useful appearance for prevention can be maximized by architectural concepts through careful analysis and concepts in every planning and design.